The Influence of Price, Promotion, and Product Quality on the Purchase Decision of Samsung Mobile Phones Among Students of Labuhanbatu University - Lestari, Dian; Nasution, Ade Parlaungan; Pohan, Muhammad Yasir Arafat (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
The purpose of this research is to examine how students at Universitas Labuhanbatu make judgements about which Samsung smartphones to buy based on factors such as price, promotion, and product quality. One hundred people filled out the survey, and the results were analysed quantitatively using multiple linear regression. According to the t-test, there is a positive and statistically significant effect of price (8.819; 0.000). There is a beneficial effect of promotion (9.066; 0.000). The most important factor is the quality of the product (12.171; 0.000). The concurrently substantial influence is confirmed by the F-test result (66.076; 0.000). The independent factors account for 67.4% of the variance in purchase decisions, according to the R² value of 0.674.